Using deep learning algorithms to detect violent activities - Ammar, S.M. Rojin; Anjum, Md. Tanvir Rounak; Islam, Md. Touhidul Islam (BRAC University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.